AT&T Inc. : a proposed merger with T-Mobile - Hunt, J. Timothy; Wang, Alex; Liu, Becky; O'Rourke, James S., 1946- (London : SAGE Publications Ltd, 2017)
In an effort to gain market share and technological resources, AT&T and T-Mobile USA agreed to a merger that would create the largest mobile carrier in the country. Concerned about preserving competition in the wireless telecommunications industry, the U.S. Department of Justice has filed a lawsuit to block the transaction. AT&Ts management must now decide how to convince stakeholders that the benefits of a deal far outweigh the risks. Without this merger, AT&T would need to find an alternative way to remain competitive.
Originally published: Hunt, T., Wang, A., Liu, B., & ORourke, J. S. (2011). AT&T Inc.: A proposed merger with T-Mobile. 11-07. Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Description based on XML content.
Keywords: elektronické knihy; electronic books; AT & T (Firm); T-Mobile USA; Cell phone services industry -- Mergers -- United States; Consolidation and merger of corporations -- United States